Upaya DPRD Kabupaten Pasuruan dalam Mensejahterakan dan Penghapusan Praktek Perkawinan Usia Anak - Dewi Masyitah (FALASIFA : Jurnal Studi Keislaman, 2017)
Child Marriage in Indonesia is still high according to UNICEF in 2015 number up to 340,000 per year. And 50,000 girls in Indonesia are married before the age of 15 years. While in East Java according to BKKBN East Java the number of early marriage in 2015 reached 3000 pairs. Likewise in Pasuruan district according to the health service in many areas in remote areas Lekok, Grati, Nguling, Wonorjo, and Tosari so this early marriage triggers the number of young widows under age (JAMUR) regional people call it that. The phenomenon of marriage of child age must be stopped and deleted by local government of Pasuruan regency through from the root of problem in detail so get solution as specified according to the problem. This should be realized in the form of strategic policy in the abolition of child marriage practices as social welfare. It is because of this problem the research is to examine and analyze how the efforts of Parliament of Pasuruan district in the welfare and abolition of Childhood Marriage Practices.Keywords: Upaya DPRD, Kesejahteraan dan Penghapusan Pernikahan Usia Anak.